The PRIMERO birth cohort: Design and baseline characteristics - Jonathan I. Witonsky, MD, MAS; Jennifer R. Elhawary, MS; Celeste Eng, BS; Sam S. Oh, PhD, MPH; Sandra Salazar; Maria G. Contreras, BS; Vivian Medina, RN, BSN, SC; Elizabeth A. Secor, MA; Priscilla Zhang, BS; Jamie L. Everman, PhD; Ana Fairbanks-Mahnke, BS; Elmar Pruesse, PhD; et al. (Journal of Allergy and Clinical Immunology: Global)
Background: Although early-life respiratory illnesses (RIs) are linked to childhood asthma, it is unclear whether children are predisposed to both conditions or if RIs induce alterations that lead to asthma. Puerto Rican children, who bear a disproportionate burden of early-life RIs and asthma, are an important population for studying this relationship. Objective: We sought to describe the design and baseline characteristics of the Puerto Rican Infant Metagenomic and Epidemiologic Study of Respiratory Outcomes (PRIMERO) birth cohort. Methods: PRIMERO is designed to examine the role of respiratory viruses on the development of RIs and asthma. Pregnant women were recruited at Hospital Interamericano de Medicina Avanzada–San Pablo in Caguas, Puerto Rico. Questionnaires at birth and annual follow-ups gather clinical, social, and environmental data. Collected samples include postterm maternal blood; infant cord blood; the child’s blood at year 2; and the child’s nasal airway epithelium at birth, during RIs over the first 2 years, and annually until age 5. Results: We enrolled 2,100 mother–child dyads into the PRIMERO study between February 2020 and June 2023, representing 59% of births at Hospital Interamericano de Medicina Avanzada. As of April 29, 2024, 2,069 participants remain active, with high rates of biospecimen collection and annual visit participation. Illness surveillance detected 6,076 RIs, with 38.4% involving the lower respiratory tract. Conclusion: The PRIMERO birth cohort study, with its comprehensive data on viral exposures, respiratory outcomes, and airway molecular phenotypes in a high-risk population of Puerto Rican children, is uniquely positioned to address long-standing questions about the early-life determinants and mechanisms underlying virus-related asthma development.